Dissolution performance improvement of fenofibrate through secondary solid dispersion using PEG6000 and croscarmellose sodium combination - Khan, Tonima Akter (BRAC University, 2016)
This project report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2016